Penerapan model pembelajaran SAVI dalam meningkatkan kemampuan berpikir kritis siswa di sekolah dasar - Sefri Setiyamara; Fitri Aida Sari; Fara Virgianita Pangadongan; Sukriadi Sukriadi; Maria Gaudensia Aldince (Program Studi Pendidikan Matematika, Universitas Nusantara PGRI Kediri, 2026)
Critical thinking skills are important competencies that need to be developed, especially at the elementary school level. However, developing these skills remains a challenge in mathematics learning. The purpose of this study is to examine the effect of the SAVI learning model on the development of primary school students' critical thinking skills. The SAVI (Somatic, Auditory, Visual, Intellectual) learning model is an approach that involves physical activity, listening, visual observation, and intellectual engagement in the learning process. This study used a quantitative approach with a quasi-experimental nonequivalent control group design. The subjects consisted of two classes: an experimental class treated with the SAVI model and a control class using conventional learning. The instruments were a pretest and a posttest. Data were analyzed using the Shapiro-Wilk normality test, Levene's test for homogeneity, and hypothesis testing. Improvement in students' critical thinking skills was measured using n-Gain to determine improvement categories in each class. The results showed that improvements in students' critical thinking skills in both groups were in the moderate range, with n-Gain scores of 0.68 in the experimental class and 0.70 in the control class. Statistical analysis using the Mann–Whitney test indicated no significant difference between the two groups (p > 0.05), with a very small effect size (r = 0.003). This finding indicates that implementing the SAVI learning model did not yield a greater impact than conventional learning. This result is influenced by several factors, including limited learning time, low student participation, decreased concentration, classroom environment, and students' readiness for higher-order thinking